Can Profitability Moderate the Impact of Green Investment, Corporate Social Responsibility, and Good Corporate Governance on Company Value on the SRI-KEHATI Index? - Paramita, V. Santi; Ali, Ashma (International Journal of Finance Research, 2023)
The Sri-Kehati Index shares, which offer shares of environmentally friendly companies, are of great interest to investors who care about the environment. This research aims to determine the determinant factors of company value in Sri-Kehati Index companies, with profitability as a moderating variable. The determinant factors used in modeling are green investment, corporate social responsibility, and good corporate governance. ROA proxied profitability, and company value is proxied by price book value. The research uses a quantitative approach with descriptive-verification methods. The research population is companies that are members of the Sri-Kehati Index 2016-2021; the sample is determined using a purposive sampling technique—data analysis techniques using panel data regression and Moderated Regression Analysis (MRA). The research results show that partially green investment and good corporate governance have a positive effect, but corporate social responsibility does not affect company value. Profitability can moderate the relationship between good corporate governance and firm value. Besides that, green investment, corporate social responsibility, and good corporate governance simultaneously influence the company value of companies that are members of the Sri-Kehati Index stock group. The results of this research can be a basis for consideration by investors who care about the environment in investment decisions and can be a reference for further research. It is hoped that the results of this research will encourage many companies to implement green investments to help overcome environmental problems.